An Investigation of the Practices of Australian Adults Experiencing Pain and Their Views of Australian Community Pharmacy Pain Management Services - John Mishriky; Ieva Stupans; Vincent Chan (MDPI AG, 2020)
Pain is a common and debilitating condition requiring appropriate assessment and management. The consequences of inadequate treatment of pain is well known; however, research investigating pain management practices and the benefits Australian community pharmacies offer in pain management are more limited. This study investigated the knowledge and practices of Australian adults experiencing pain, and their views of community pharmacy pain management services. A cross-sectional study was conducted using a pre-tested anonymous self-administered questionnaire. Participants were recruited from ten community pharmacies across metropolitan Melbourne, Australia. A total of 120 participants completed the questionnaire. Most reported that their pain interfered with their quality/functionality-of-life. Paracetamol was the pharmacological preference irrespective of pain severity experienced. Approximately 30% did not believe that visiting a community pharmacy is helpful in pain management, but many reported their pain management knowledge could be improved, yet more than 60% disagreed when asked whether they would rather visit a supermarket than their pharmacy to purchase analgesics. More than half believed that community pharmacies can and should offer more pain management services. This suggests that enhancing the involvement of community pharmacists can help bridge gaps in pain management knowledge, which may provide greater positive outcomes for patients experiencing pain symptoms.